Pengembangan Lembar Kerja Siswa (LKS) Berbasis Nilai-Nilai Moral untuk Pembelajaran Matematika Kelas 2 SDK 6 Penabur - Leo Nuter Tanaleppy (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The purpose of this research is to develop the teaching material based the value of moral blemish so as to the value of learning mathematics grade II primary school with matter a addition and subtraction, a unit of or value place , and the name & symbol of the number. The study is done at grade II students from SDK 6 PENABUR, North Jakarta. A model research used to develop, this is the kind of MPI media. In this research products then tried out on one person the people of the design , material of two experts , language of two experts. On the results of the tryouts linguist obtained decided how much 93%, while the people of the design to learning mathematics test decided how much 84%, and the people of the material to learning mathematics decided how much 83 % and test the people of the material from teachers to learning mathematics grade II students from SDK 6 PENABUR, North Jakarta with decided how much 89%. This suggests that teaching material based the value of moral for teaching mathematics grade II with matter a addition and subtraction, a unit of or value place , and the name & symbol of the number, supporting used as a learning math.